Analisis Perbandingan Efisiensi Pada Bank Syariah di Indonesia dan Malaysia Dengan Pendekatan Data Envelopment Analysis (DEA) - Hikmah, Siti Nurul; Jannah, Mukhlishotul; Elsa, Elsa (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2024)
This study analyzes the efficiency of Islamic banks in Indonesia and Malaysia from 2019 to 2022 using the Data Envelopment Analysis (DEA) method. The input variables include total assets, equity, and operational costs, while the output variables are financing and net profit. By analyzing data from five Islamic banks in each country, this study compares efficiency levels, highlights changes during the COVID-19 pandemic, and identifies factors contributing to inefficiency. The analysis shows that some banks maintained full efficiency, while others experienced a decline due to increased operational costs and lower profitability, especially during the pandemic. This study aims to analyze the efficiency of Islamic banks in Indonesia and Malaysia using the Data Envelopment Analysis (DEA) method. The study uses financial data from Islamic banks in Indonesia and Malaysia from 2019 to 2022. The results show that Islamic banks in Indonesia have lower efficiency levels than those in Malaysia.